UNVEILING THE RELATIONSHIPS BETWEEN RESPONSIBLE AND IMPACTFUL CORPORATE HUMAN RESOURCE PRACTICES, ENTREPRENEURIAL EXIT INTENTIONS AND PERCEIVED BARRIERS: EXPLORING THE ROLE OF GENDER (Contemporary Journal of Social Science Review, 2025)
Purpose- The study unveiled and examined the relationship between human resource investment, perceived barriers, and entrepreneurial intentions, with gender acting as a regulatory player. The study also extended of the existing literature on entrepreneurship by focusing on how the investment of resources and perceived barriers affect EEI.   Methodology-Researcher used a quantitative research design along with other methodologies to carry out this study and the primary data collection tool used was questionnaire. A hyperlink was used to contact 440 Lahore-based entrepreneurs who were interested in taking part in this study. Of the 440 respondents or 91% who received the survey link, 403 people answered the questionsFindings- Based on participant demographic data, it was observed that the sample's gender, age, and qualifications were diverse. The constructs' validity and reliability were validated by the measurement model analysis, indicating that they are appropriate for additional study. Significant correlations between Developing Resources (DR) and Perceived Barriers (PB), DR and Entrepreneurial Exit Intentions (EEI), and PB and EEI were found during the structural model evaluation. The report suggested that males exhibit higher exit entrepreneurship indicators than females, which emphasizes the role of gender as a moderating variable in the relationship between perceived barriers and enterprise intentions.Practical implementations- The current study practically contributed by critically and rationally examining the relationship among EEE, perceived hurdles, and resource investment. This is significant because it bears on determinants like performance, competition across industries, and organizational innovation.Originality/Value- The study advocates that identifying and addressing the perceived barriers to entrepreneurial exit may increase organizational support toward aspiring entrepreneurs, which may become more tolerant, understanding, and supportive. The study also seeks to contribute toward making the assessment of sustainable entrepreneurship more comprehensive and gender sensitive.